2021
DOI: 10.1021/acsnano.1c03312
|View full text |Cite
|
Sign up to set email alerts
|

Two-Dimensional Magnets beyond the Monolayer Limit

Abstract: Intrinsic two-dimensional (2D) magnetism has been demonstrated in various materials scaled down to a single monolayer. However, the question is whether 2D magnetism extends beyond the monolayer limit, to chemical species formed by sparse but regular 2D arrays of magnetic atoms.Here we show that sub-monolayer superstructures of Eu atoms self-assembled on the silicon surface exhibit strong magnetic signals. Robust easy-plane magnetism is discovered in both one-and two-dimensionally ordered structures with Eu cov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
34
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 54 publications
1
34
0
1
Order By: Relevance
“…In the experiment, Tokmachev et al observed that the sub-monolayer of Eu atoms selfassembled on the silicon surface exhibited an easyplane magnetism. 9 Similar easy-plane magnetisms were also detected in Eu/graphene, 10 Eu/silicene, 11 and Eu/germanene systems. 12 However, their T BKT are smaller than 20 K. [9][10][11][12] Pinto et al demonstrated a BKT phase transition in monolayer CrCl 3 grown on graphene/6H-SiC(0001) substrate with T BKT of 12.95 K, 13 which is consistent with Lu' s prediction 14 .…”
mentioning
confidence: 57%
See 1 more Smart Citation
“…In the experiment, Tokmachev et al observed that the sub-monolayer of Eu atoms selfassembled on the silicon surface exhibited an easyplane magnetism. 9 Similar easy-plane magnetisms were also detected in Eu/graphene, 10 Eu/silicene, 11 and Eu/germanene systems. 12 However, their T BKT are smaller than 20 K. [9][10][11][12] Pinto et al demonstrated a BKT phase transition in monolayer CrCl 3 grown on graphene/6H-SiC(0001) substrate with T BKT of 12.95 K, 13 which is consistent with Lu' s prediction 14 .…”
mentioning
confidence: 57%
“…9 Similar easy-plane magnetisms were also detected in Eu/graphene, 10 Eu/silicene, 11 and Eu/germanene systems. 12 However, their T BKT are smaller than 20 K. [9][10][11][12] Pinto et al demonstrated a BKT phase transition in monolayer CrCl 3 grown on graphene/6H-SiC(0001) substrate with T BKT of 12.95 K, 13 which is consistent with Lu' s prediction 14 . On the theoretical side, easy magnetization plane has predicted in monolayer VSi 2 N 4 with a T BKT of 307 K 15 and monolayer FeX 2 (X = Cl, Br, and I) with maximum T BKT of 210 K. 16 The T BKT of 2D VSi 2 N 4 and FeX 2 15,16 has large uncertainty because they were estimated by a classical 2D XY model which only considers nearest-neighboring magnetic coupling and constrains the spin into the xy plane.…”
mentioning
confidence: 57%
“…According to ref. 32, magnetic properties of Eu reconstructions on Si(001) covered by Al remain stable for at least 5 years.…”
Section: Resultsmentioning
confidence: 99%
“…31 Recently, 4 distinct large-scale regular phases of Eu on Si(001) have been synthesized and scrutinized with respect to their magnetic properties. 32 It turns out that the 3 phases with the Eu coverage exceeding 1/2 ML exhibit magnetic properties whereas the only phase with a low Eu coverage does not (in this context the coverage is a function of the regular structure/stoichiometry of the Eu phase). The 3 magnetic phases of Eu on Si(001) have a common structural motif – they are formed by identical rows of Eu atoms; spaces between the rows are however different.…”
Section: Introductionmentioning
confidence: 99%
“…Commercial general-purpose superconducting quantum interference devices (SQUID) have become ubiquitous experimental tools in laboratories where magnetic characterization and investigations of nanometer-scale objects is important and frequently indispensable in providing the vital insight into investigations. The range of objects include, in particular, ultrathin films [1,2], nanoparticles [3,4], and inclusions in magnetically dilute systems [5][6][7], 2D [8,9], and 1D [10,11] systems, or systems in which their surface matters [12], like topological insulators [13][14][15]. In the prevailing number of cases, the materials of interest are on a solid state substrate, which make the mounting of the sample relatively easy; a breadth of relevant experimental codes has been elaborated and methods for eliminating various pitfalls have been presented [16][17][18][19][20], which were reviewed by Pereira [21].…”
Section: Introductionmentioning
confidence: 99%